Description of Sweetened Beverage Consumption in Obese Adolescents - Rahendra, Karina; Putri, Syeptri Agiani; Novayelinda, Riri (Jurnal Keperawatan Profesional, 2025)
Obesity is a global health problem with increasing prevalence. One behavioral factor contributing to the risk of obesity in adolescents is the consumption of sugary drinks. The 2018 Basic Health Research (Riskesdas) data shows that 61.27% of the population aged ≥3 years consumed sugary drinks more than once a day, 30.22% consumed them 1–6 times per week, and only 8.51% consumed them less than three times per month. This study aims to describe the consumption patterns of sweetened drinks in obese adolescents. The study used a quantitative descriptive design with a cross-sectional approach. The study sample consisted of 70 obese adolescents selected through a total sampling method according to the inclusion criteria. Data were collected using a respondent characteristics questionnaire and the Beverage Intake Questionnaire (BEVQ-15), then analyzed univariately. The results showed that of the 70 respondents, 38 (54.3%) were male and 32 (45.7%) were female. The majority of respondents aged 14 (58.6%), and 53 (75.7%) reported high levels of sweetened beverage consumption. High frequency and volume of consumption contribute to increased daily calorie intake, a risk factor for obesity. Awareness-raising and control efforts regarding sweetened beverage consumption are needed as a strategy for obesity prevention from adolescence..